2008
DOI: 10.1590/s0102-09352008000400014
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal effect of three pasture plants species on the free-living stages of Haemonchus contortus

Abstract: To evaluate both the development and survival of free-living stages of Haemonchus contortus obtained from feces of infected ovine in the four seasons of the year, eggs of this nematode were deposited on three grass species commonly used as sheep pasture in Brazil (Brachiaria decumbens cv. Australian, Cynodon dactylon cv. Coast-cross, and Panicum maximum cv. Aruana). The grasses were cut 5 or 30cm height before depositing the feces. Samples of grasses and feces were collected in six sub-plots from each plot one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 10 publications
(8 reference statements)
6
21
0
7
Order By: Relevance
“…Carneiro and Amarante (2008), in a study carried out in the same site of the present experiment, also observed higher recovery of H. contortus L3 from 30 cm high Aruana herbage at the moment of contamination. Rocha et al (2008), however, did not find influence of the herbage height on the recovery of T. colubriformis L3 in the summer.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Carneiro and Amarante (2008), in a study carried out in the same site of the present experiment, also observed higher recovery of H. contortus L3 from 30 cm high Aruana herbage at the moment of contamination. Rocha et al (2008), however, did not find influence of the herbage height on the recovery of T. colubriformis L3 in the summer.…”
Section: Discussionsupporting
confidence: 82%
“…In general, Aruana herbage favored the highest L3 concentrations compared to the remaining herbage species, which was also observed for H. contortus L3 by Carneiro and Amarante (2008). Brachiaria and Coast-cross were the densest herbage species, which probably led to an effect of dilution of L3 with lower availability of infective larvae.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…O resultado para o pastejo alternado está de acordo com o encontrado por Fernandes et al (2004). Em condições favoráveis, as larvas infectantes podem sobreviver durante várias semanas ou até vários meses no ambiente (Souza et al, 2000;Rocha, 2006;Carneiro & Amarante, 2008).…”
Section: Resultsunclassified
“…Estes resultados são de grande relevância no controle da verminose em ovinos sob pastejo, face à menor ingestão de L3 nos relvados mantidos com alta densidade forrageira. No entanto, outros aspectos relacionados às características nutricionais das forragens também devem ser levados em consideração, pois animais em boas condições nutricionais têm maior capacidade para resistir às infecções por nematóides gastrintestinais (COOP; KYRIAZAKIS, 2001).…”
Section: Discussionunclassified